2016
DOI: 10.1371/journal.pone.0148766
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Progenitor Cells and Clinical Outcome in Patients with Aortic Stenosis

Abstract: BackgroundAortic stenosis (AS) is the most common valvular disease. Endothelial progenitor cells (EPCs) have a role in the repair of endothelial surfaces after injury. Reduced numbers of EPCs are associated with endothelial dysfunction and adverse clinical events, suggesting that endothelial injury in the absence of sufficient repair by circulating EPCs promotes the progression of vascular and possibly valvular disorders. The aim of this study was to assess EPC number in patients with AS and to study the predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
(36 reference statements)
1
5
1
Order By: Relevance
“…The results showed that AAD patients had decreased number and migration or proliferation of EPCs. However, our findings may be the different from that of Van Spyk E N's ( 37 ), and the possible reasons may be as follows: First, there is a difference in enrolled subjects. although commonly pathogenesis of AAD is atherosclerosis and share similar as the abdominal aortic aneurysm (AAA).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The results showed that AAD patients had decreased number and migration or proliferation of EPCs. However, our findings may be the different from that of Van Spyk E N's ( 37 ), and the possible reasons may be as follows: First, there is a difference in enrolled subjects. although commonly pathogenesis of AAD is atherosclerosis and share similar as the abdominal aortic aneurysm (AAA).…”
Section: Discussioncontrasting
confidence: 88%
“…Numerous studies have indicated that the EPCs may predict outcomes in cardiovascular disease ( 35 , 36 ). It has been proven that the levels of CD34+ cells are altered in patients with abdominal aortic aneurysms compared with patients with peripheral vascular disease, and the CD34+ cells were correlated with aneurysm diameter ( 37 , 38 ). However, few studies focus on the relationship between circulating EPCs and AAD.…”
Section: Discussionmentioning
confidence: 99%
“…Shimoni et al observed that low circulating EPCs levels were associated with cardiac death in patients with aortic stenosis (AS). They suggested that the lower numbers of circulating EPCs may be due to increased cell senescence as well as stimulation of circulating EPCs apoptosis in AS patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Low CD34 þ VEGFR2 þ EPCs portended adverse cardiovascular outcomes in patients with aortic stenosis. 95 Additionally, low CD34 þ , CD133 þ , and CD34 þ CD133 þ HSPCs are independently associated with a nearly two-fold risk of cardiovascular events in diabetic individuals, 96 and CSC depletion was associated with adverse cardiovascular outcomes among Asian patients on haemodialysis. 97,98 Figure 4 shows the forest plot of an updated meta-analysis of longitudinal studies involving 100þ patients (from Supplementary material online, Table S1) and reporting poolable estimates of the hazard ratio for cardiovascular events, cardiovascular death, and all-cause death associated with low CSC levels.…”
Section: Circulating Stem Cells and Outcomes In Patients With Cardiov...mentioning
confidence: 99%